Quantum transport through impurity clusters in carbon nano-materials - McIntosh, Ross William (My University, 2014)
Modified graphene and low dimensional carbon nano-electronic devices have the potential to supersede current technologies in many respects although manufacturing and understanding these materials poses a significant challenge which requires an incremental approach. Doping of graphene, a prerequisite for modifying the electronic properties, is still poorly understood.Band-modulation is therefore difficult to control. Resonant tunneling induced through the incorporation of impurity clusters has not yet been addressed. On the other hand electronspin correlations in modified graphenes have hardly been studied. In this work we address these issues through a tandem approach of theoretical and experimental studies. This work begins with an ab-initio study of the electronic properties of bilayer graphene and the modifications induced through the substitutional incorporation of isolated nitrogen impurities.Nitrogen modification results in a change from a zero-gap semiconductor to a metal as a result of nitrogen incorporation while charge density calculations show the localization of charge in the vicinity of the impurity. This work on isolated impurities was then extended to impurity clusters. The quantum transport properties of impurity clusters distributed within a high bandgap material were then studied. Different geometrical configurations of the impurity clusters were studied to tune quantum interference to control the carrier lifetime. The effects of randomly distributed clusters were also studied to interpret the effects of disorder. These studies provide insight into the transport properties of naturally grown quantum dot systems such as reduced graphene oxide which consists of low defect density graphene nano-islands randomly distributed in oxygen and free radical functionalized graphene which was studied experimentally. Resistance was recorded as a function of temperature for graphene oxide and reduced graphene oxide two terminal devices. Evidence of mesoscopic resistance fluctuations, charge carrier activation and enhanced elastic scattering was found while the magnetic properties of reduced graphene oxide showed a phase transition from ferromagnetism at low temperatures to diamagnetism at higher temperatures. Finally, the Kondo effect was demonstrated in reduced graphene oxide through transport and magnetoresistance measurements which were interpreted within the Fermi liquid description of the Kondo effect. These effects were explained through the microstructure of reduced graphene oxide and illustrate the significance of spin in reduced graphene oxide. These studies will inform the design of functionalized graphene spin-polarized devices and spin valves.
Keywords: Nanoelectronics.; Nanoelectronics - Materials.; Graphene.; Carbon.